Keberagamaan Napi di Lembaga Pemasyarakatan Perempuan Kelas II A Kota Bandung - Husnul Koimah; Yeni Huriani (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2021)
This study discusses the religious behavior of female prisoners in the Class IIA Women's Penitentiary in Bandung City. Through qualitative methods with data collection by observation and interviews, this research answers how the religious behavior of female prisoners when in prison. This religious behavior is seen in three aspects: the form of thought, the form of action, and the form of fellowship. This study found that prisoners believe that their presence in prison is the right place to cleanse themselves with religious messages. In religious behavior, the prisoners think fully believe in each God, scriptures, prophets, angels, and their religious doctrines, especially Islam and Christianity. In the form of actions, the coaching program provided by prisons is quite effective in increasing religious behavior through ‘shalihah’ pesantren activities, iqra classes, tausiyah, and worship services. The program is beneficial for prisoners in forming a more responsible character. Finally, religious behavior in fellowship is a complementary form of religious forms of thought and action. Through this form of fellowship, inmates are more stable when socializing with fellow inmates and prison officers.